Men, Masculinities and Male Culture in the Second World War (Genders and Sexualities in History, 2018)
This edited collection brings together cutting-edge research on British masculinities and male culture, considering the myriad ways British men experienced, understood and remembered their exploits during the Second World War, as active combatants, prisoners and as civilian workers. It examines male identities, roles and representations in the armed forces, with particular focus on the RAF, army, volunteers for dangerous duties and prisoners of war, and on the home front, with case studies of reserved occupations and Bletchley Park, and examines the ways such roles have been remembered in post-war years in memoirs, film and memorials. As such this analysis of previously underexplored male experiences makes a major contribution to the historiography of Britain in the Second World War, as well as to socio-cultural history, cultural studies and gender studies.